Kant on the Frontier : Philosophy, Politics, and the Ends of the Earth - Bennington, Geoffrey (Book collections on Project MUSE., 2017)
Frontier: the border between two countries; the limits of civilization; the bounds of established knowledge; a new field of activity. At a time when all borders, boundaries, margins, and limits are being-often violently-challenged, erased, or reinforced, we must rethink the concept of frontier itself. But is there even such a concept? Through an original and imaginative reading of Kant, Geoffrey Bennington casts doubt upon the conceptual coherence of borders. The frontier is the very element of Kant's thought yet the permanent frustration of his conceptuality. Bennington brings out the frontier's complex, abyssal, fractal structure that leaves a residue of violence in every frontier and complicates Kant's most rational arguments in the direction of cosmopolitanism and perpetual peace. Neither a critique of Kant nor a return to Kant, this book proposes a new reflection on philosophical reading, for which thinking the frontier is both essential and a recurrent, fruitful, interruption.